Dampak Faktor Eksternal terhadap Kesejahteraan Rumah Tangga Petani Tebu Keprasan di Jawa Tengah - Fadilla Ristya Aminda; Bonar Marulitua Sinaga; Anna Fariyanti (Jurnal Agro Ekonomi, 2017)
EnglishCentral Java Province is one of sugarcane producing centers in Indonesia and Pati is one of sugarcane producing regencies in the province. A total of 5,905 households in Pati regency conduct sugarcane farming as their primary income source. However, sugarcane farmers deal withlimited capital to adopt productivity improving technologies. This study aimed to analyze factors influencing economic decisions of sugarcane farmers in allocating working hours, production, and household’s expenditure, as well as to analyze the impact of changes in input prices, output price, credit, and sugar level on sugarcane farmer household’s welfare in Central Java. Simultaneous equation models consisting of 21 structural equations and 22 identity equations were estimated using Two-Stage Least Squares (2SLS) method. The results showed that an increase in credit, sugar price, and sugar level could compensate increases in fertilizer price and labor wage and had positive impact on farmers’ welfare. Increases in fertilizer price and labor wage could be compensated through credit, sugar price, and sugar level enhancement. It is necessary that the Government increases sugar price and ensures farmers’ access to credit. It aims to encourage farmers to adopt technology through replanting (ratoon replacement) to improve sugarcane productivity and farmers’ welfare.IndonesianJawa Tengah merupakan salah satu sentra produksi tebu di Indonesia. Salah satu kabupaten sentra produksi tebu di Jawa Tengah adalah Pati. Sebanyak 5.905 rumah tangga petani tebu di Kabupaten Pati memiliki usaha tani tebu sebagai sumber pendapatan utama. Rumah tangga petani tebu dihadapkan pada masalah keterbatasan modal sehingga kemampuan adopsi teknologi rendah dan budi daya tidak optimal. Kondisi ini berdampak pada rendahnya produktivitas dan pendapatan rumah tangga. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi keputusan ekonomi rumah tangga petani tebu dalam alokasi curahan kerja, produksi, dan pengeluaran rumah tangga, serta dampak perubahan harga input, harga ouptut, kredit, dan rendemen terhadap kesejahteraan rumah tangga petani tebu. Penelitian menggunakan data cross section dengan jumlah sampel sebanyak 56 rumah tangga petani tebu. Model ekonomi rumah tangga petani dibangun sebagai sistem persamaan simultan yang terdiri dari 21 persamaan struktural dan 22 persamaan identitas, lalu diestimasi menggunakan metode Two Stage Least Squares (2SLS). Hasil penelitian menunjukkan bahwa kebijakan peningkatan harga gula, jumlah kredit, dan rendemen gula berdampak positif terhadap kesejahteraan rumah tangga petani. Peningkatan harga pupuk dan upah tenaga kerja luar keluarga mampu dikompensasi dengan peningkatan jumlah kredit, harga gula, dan rendemen gula. Pemerintah sebaiknya meningkatkan harga patokan petani dan juga memperbesar jumlah kredit yang dapat diakses petani untuk mendorong adopsi teknologi dengan melakukan peremajaan tanaman (bongkar ratoon) yang bertujuan untuk meningkatkan produktivitas dan kesejahteraan rumah tangga.